Pembangunan dan penilaian keberkesanan modul pementoran Islam rakan sebaya terhadap personaliti beragama pelajar universiti - Noraini, Ismail (2024)
Human development programs in universities have been the government's agenda since the 9th Malaysia Plan (RMK9). Even so, various issues involving students have disrupted the efforts. Among them is the issue of university students' religious personality, which needs to be improved to realize the national agenda. The study also shows that implementing modular religious guidance to improve the religious personality of university students requires a more comprehensive effort. Therefore, the objectives of this study are to construct an Islamic peer mentoring module, obtain its validity and reliability, and test its effectiveness in shaping the religious personality of university students. Construction procedures, as well as module effectiveness tests using Sidek and Jamaluddin models (2005), while The Muslim Religiosity-Personality Inventory (MRPI) (2005) and al-Ghazali's religious personality model (1988) were used to develop the content. This study combines qualitative and quantitative approaches containing the module construction and testing effectiveness phases. First, module requirements were studied, and then the module was built based on the selected model. Second, the validity and reliability values of the module and instrument were obtained, and the module's effectiveness was tested. This quasi-experimental study involving 60 experimental subjects and 60 control subjects showed that this module effectively forms university students' religious personalities. T-tests and One-way ANOVA showed significant differences in the pre-test and post-test between the experimental and control groups. In contrast, the T-test and ANCOVA analysis showed no difference in the module effect between male and female experimental groups. This study has produced a complete draft of the Islamic Peer Mentoring Module and an instrument based on five sub-scales of religious personality. It also contributes to the new initiative of implementing modular and more systematic Islamic peer mentoring, especially in universities.